2019
DOI: 10.5505/ktd.2019.05826
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: INTRODUCTION ÖZ GİRİŞ ve AMAÇ: Bu çalışmada uzmanlık eğitimi sonrası PNL'ye ilk kez 2. basamak devlet hastanesinde başlayan bir cerrahın bu cerrahide yetkinliğe ulaşıldığı düşünülen ilk 60 vakasının sonuçlarını retrospektif olarak değerlendirerek PNL'ye 2. basamak hastanelerinde güvenli ve etkin bir şekilde başlanabileceğini değerlendirmek amaçlandı. YÖNTEM ve GEREÇLER: Çalışmaya perkütan nefrolitotomi yapılan 60 renal ünite (58 hasta) dahil edildi. Tüm hastalara prone pozisyonda standart (30Fr) perkütan nefro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In some kidney stones, daily and ambulatory PNL can also be performed in selected cases [18,19]. In our study, the length of stay of the patients was 2.7 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). We see that this period is prolonged in patients with high stone surface area, long surgical time, or unwanted side-effects and requiring additional treatment.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In some kidney stones, daily and ambulatory PNL can also be performed in selected cases [18,19]. In our study, the length of stay of the patients was 2.7 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). We see that this period is prolonged in patients with high stone surface area, long surgical time, or unwanted side-effects and requiring additional treatment.…”
Section: Discussionmentioning
confidence: 57%
“…The success rate was reported as 80% in the study conducted in the 2nd stage state hospital by Benli et al [10]. In the study conducted by Bıçaklıoğlu et al [5], this rate was observed to be 83.3%. In our study, the stone-free rate was observed to be 84.3% when clinically insignificant residual fragments and the presence of residual stones were The overall success rate was 93.1%.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation